In vitro mechanism for down-regulation of ERalpha expression by epigallocatechin gallate in ER+/PR+ human breast cancer cells - De Amicis, Francesca (Mol Nutr Food Res, 2013)
SCOPE: Exposure of the breast to estrogens and other sex hormones is an important cancer risk factor and estrogen receptor down-regulators are attracting significant clinical interest. Epigallocatechin gallate (EGCG), a polyphenolic compound found in green tea, has gained considerable attention for its antitumor properties. Here we aimed to investigate the molecular mechanisms through which EGCG regulates ERα expression in ER+ PR+ breast cancer cells. MATERIAL AND METHODS: Western blotting analysis, real time PCR and transient transfections of deletion fragments of the ERα gene promoter show that EGCG down-regulates ERα protein, mRNA and gene promoter activity with a concomitant reduction of ERα genomic and non genomic signal. These events occur through p38(MAPK)/CK2 activation, causing the release from Hsp90 of PR-B and its consequent nuclear translocation as evidenced by immunofluorescence studies. EMSA and ChIP assay reveal that, upon EGCG treatment, PR-B is recruited at the half PRE site on ERα promoter. This is concomitant with the formation of a corepressor complex containing NCoR and HDAC1 while RNA polymerase II is displaced. The events are crucially mediated by PR-B isoform, since they are abrogated with PR-B siRNA. CONCLUSIONS: Our data provide evidence for a mechanism by which EGCG down-regulates ERα and explain the inhibitory action of EGCG on the proliferation of ER+ PR+ cancer cells tested. We suggest that the EGCG/PR-B signaling should be further exploited for clinical approach.